2014
DOI: 10.1055/s-0034-1365828
|View full text |Cite
|
Sign up to set email alerts
|

Important Anatomical Relationships of the Posterior Interosseous Nerve in the Distal Forearm for Surgical Planning: A Cadaveric Study

Abstract: A thorough knowledge of the anatomy of the terminal branch of the posterior interosseous nerve (PIN) and its relationship to the anterior interosseous nerve (AIN) is essential in facilitating regional anesthetic blocks as well as in planning surgical exposures for wrist surgery. Division of the PIN has been recommended in patients with persistent wrist pain who have not responded to conservative treatment and whose physical demands are low. 1 Denervation of the PIN is undertaken as an adjunct to salvage proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
(21 reference statements)
0
8
0
Order By: Relevance
“…Jariwala et al's (2014) study of Thompson's approach to the forearm noted that the posterior interosseous nerve (PIN) was consistently found in the 4th extensor compartment in all 30 cadavers and noted the proximity of the AIN to PIN. The mean anterior–posterior distance was 0.28 cm (±0.02) between the two nerves.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Jariwala et al's (2014) study of Thompson's approach to the forearm noted that the posterior interosseous nerve (PIN) was consistently found in the 4th extensor compartment in all 30 cadavers and noted the proximity of the AIN to PIN. The mean anterior–posterior distance was 0.28 cm (±0.02) between the two nerves.…”
Section: Resultsmentioning
confidence: 99%
“…Grechenig et al (2017) showed these nerves were closest to one another at 8 cm proximal to the RS and a mean 0.84 cm (±0.23) from the ulnar edge of the radius. Jariwala et al (2014) highlighted in their study the proximity of the last motor branch of the PIN to the ulnar head (4.7 cm ± 0.84) and showed the last motor branch of the PIN supplied the extensor indicis in 70% of cases and extensor pollicis longus (EPL) in 30%.…”
Section: Posterior Interosseous Nervementioning
confidence: 97%
See 2 more Smart Citations
“…Jariwala et al 20 and Carr and Davis 11 demonstrated that the diameter of PIN increases distally. In our study, some samples might have been collected at slightly different levels, which might have influenced the fascicular area and fiber density measurements.…”
Section: Discussionmentioning
confidence: 99%